A brief overview about the use of different bioactive liposome-based drug delivery systems in Peritoneal Dialysis and some other diseases. (12th May 2021) - Singh, Sandeep Kumar; Kumar, Umesh; Guleria, Anupam; Kumar, Dinesh
Abstract: Peritoneal dialysis (PD) is a promising way of treatment used for patients suffering from End-Stage Renal Failure (ESRF). Liposomes are nanocarriers comprised of lipid bilayers encapsulating an aqueous core. Liposomes are extensively used as drug delivery systems and several liposomal nanomedicines have been approved for clinical applications. Nanomedicine constitutes a new direction in peritonitis prevention using peritoneal dialysis (PD). In case of PD; there is a more risk of bacterial infection in the peritoneal cavity along with subcutaneous tunnel and catheter existing site. These infections are the most common complications associated with prolonged peritoneal dialysis (PD) therapy. To prevent such complications, patients used to treat with suitable antibiotic. Nanocarriers consist of assembly of nano-sized vehicles planned to deliver encapsulated/loaded bioactive(s) to the specific target (tissues or organs) and have provided prominent improved therapeutic efficacy for PD patients. The advantage of bioactive loaded nanocarrier has the efficient capacity to deliver at target specific site in PD. This review focuses mainly on the current use of different liposomal encapsulated bioactive compounds in drug delivery systems in the case of PD and other human diseases and briefly highlights the importance and use of different liposomal encapsulated antimicrobial agents to improve the PD technique.